Evaluasi Manajemen Pengelolaan Layanan Pengaduan Masyarakat Berbasis Teknologi Informasi pada Layanan "Sambat Online" menggunakan Framework COBIT 5 - Muhammad Hasbi Ashshiddiqi; Suprapto Suprapto; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The Malang City Goverment through the Malang City Communication and Information Office as the manager of public communication, utilizes information technology by creating a technology based public complaint service called, Sambat Online. This service allows the public to submit complaints about facilities and infrastructure in the city of Malang. However there are still problems that are owned namely, management carried out by related parties with less attention to document documentation activities regarding the requirement of defining needs and requirements for making service solutions. Therefore, information technology evalution activities are carried out using the COBIT 5 framework and focus on the BAI (Build, Acquire and Implementation) subdomain process, the selected processes were BAI02 (manage requirements definition) and BAI03 (manage solutions identification and build). The research was implemmented to set the value of the capability level also value of the GAP that occurred. The result show that the capability level value of the BAI02 and BAI03 subdomains is level 0 and there is a GAP value based on the targer level is 2. In order for the Malang City Communication and Information Agency to achive the expected target level, recommendations are given to complete documentation of base practice documents and work product according to process BAI02 and BAI03 subdomains, and create more detailed and detailed procedures related to the definition of service requirements.